Determination of distribution constants of antioxidants by electrokinetic chromatography - Váňová, Jana; Liimatta, Laura J.; Česla, Petr; Wiedmer, Susanne K. (Taylor and Francis, 2017)
Liposome electrokinetic chromatography and micellar electrokinetic chromatography were used for studying the lipophilic properties of natural antioxidants, specifically phenolic acids and flavonoids. The employed negatively charged liposomes were composed of mixtures of 1-palmitoyl-2-oleyl-sn-glycerophosphati-dylcholine and 1-palmitoyl-2-oleoyl-sn-phosphatidylserine or 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylglycerol. In micellar electrokinetic chromatography, sodium dodecyl sulphate micelles were used as the pseudostationary phase. The retention factors of the studied compounds were determined at pH 7.4. The corresponding distribution constants were calculated from the experimentally determined retention factors and the phase ratios of the liposome dispersions and the micellar system. The distribution constants between the aqueous phase and the liposomes or micelles were compared with octanol/water partition or distribution constants of the studied compounds, which were predicted using the ACD/Labs Percepta Platform-PhysChem Module. Our results indicate that the correlations between the distribution constants of the two tested liposome systems were much stronger than those between the liposome/micellar systems. The correlations between the n-octanol phase and the liposome phases were similar to that between n-octanol and the micellar phase. Our data shows that electrokinetic chromatography is an efficient method for determining partition coefficients of compounds, but the type of pseudostationary phase has a clear impact on the values.
Stanovení distribučních konstant antioxidantů pomocí elektrokinetické chromatografie
Keywords: antioxidants; distribution constants; electrokinetic chromatography; liposome; retention factors; antioxidanty; distribuční konstanty; elektrokinetická chromatografie; liposom; retenční faktory